2000
DOI: 10.1111/0735-2166.00036
|View full text |Cite
|
Sign up to set email alerts
|

Black Residential Segregation in the City and Suburbs of Detroit: Does Socioeconomic Status Matter?

Abstract: According to ecological theory, the socioeconomic status of a minority group is inversely related to the group's level of residential segregation from the majority group. This article determines whether the level of black socioeconomic status is related to the level of black residential segregation in the city of Detroit and Detroit's suburbs. Data were obtained from the U.S. Bureau of Census, 1990 Summary Tape Files 4-A. The methods employed to measure residential segregation were the indexes of dissimilarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 19 publications
3
78
0
1
Order By: Relevance
“…Yet it is almost certain that racial profiling occurs in these smaller areas (Alba & Logan, 1993;Darden & Kamel, 2000;Meehan & Ponder, 2006;Weitzer, 2000a;. Many of these smaller agencies are unable, as well, to take advantage of any likely benefits of the presence of African American police officers due to their noted absence in their force matrices.…”
Section: Racial Profilingmentioning
confidence: 99%
“…Yet it is almost certain that racial profiling occurs in these smaller areas (Alba & Logan, 1993;Darden & Kamel, 2000;Meehan & Ponder, 2006;Weitzer, 2000a;. Many of these smaller agencies are unable, as well, to take advantage of any likely benefits of the presence of African American police officers due to their noted absence in their force matrices.…”
Section: Racial Profilingmentioning
confidence: 99%
“…For example, research on social threats has demonstrated that communities respond to the greater residential presence of minorities by increasing police expenditures (P. Jackson, 1989Jackson, , 1992Liska, 1992). Community support is also reflected in gatekeeping practices that have produced patterns of residential segregation of African Americans that are deeply entrenched throughout the United States (Alba & Logan, 1993;Darden & Kamel, 2000;Massey & Denton, 1993). Although patterns of residential segregation have changed over the past 30 years--statistics show that 1 in 3 African Americans now live in suburbs--American suburbs are still predominantly white Downloaded by [University of Kent] at 17:13 16 November 2014 (Baldassare, 1992;Thernstrom & Thernstrom, 1997).…”
Section: Race and Placementioning
confidence: 99%
“…For example, as of 1990 blacks and whites were less segregated in general and at comparable income levels in Southern California's suburban counties than in the central county, which is Los Angeles (Clark and Ware 1997). This pattern is not necessarily true everywhere, though, and might be dependent on the areal units defining suburbs, as shown by the fact that within Wayne County, Michigan, blacks and whites of the same income levels were less segregated in Detroit than in areas outside that city (Darden and Kamel 2000).…”
Section: Findings From Previous Researchmentioning
confidence: 98%